Theorizing medieval race Saracen representations in old French literature - Turner, Victoria (Research monographs in French studies, 2019)
In today's discussions of religious difference and intolerance, the Middle Ages are often presented as a time of fixed racial, religious, and cultural identities, especially as regards the East and Islam. Representations of Saracens, however, show how literary traditions invite a more nuanced consideration of the complex and often surprising ways in which such non-Christian figures might be depicted. In a wide-ranging study of Old French texts from c.1150-1350, Victoria Turner explores how racial identity is not only paradoxical but even fluid in the medieval Christian literary imagination, where Arthurian heroes may have Saracen ancestors and where a Saracen may set an example of good Christian behaviour. Drawing on modern critical theory, Turner adopts a series of approaches to the term ‘race’ to counter suggestions that these medieval identities were necessarily adversarial, consistent or absolute.